Microwave-assisted biodiesel production using UiO-66 MOF derived nanocatalyst: process optimization using response surface methodology - Gouda, Shiva Prasad; H. Anal, Jasha Momo; Kumar, Puneet; Dhakshinamoorthy, Amarajothi; Rashid, Umer; Rokhum, Samuel Lalthazuala (Multidisciplinary Digital Publishing Institute, 2022)
The present work is on the transesterification of soybean oil to biodiesel under microwave irradiation using a biomass and MOF−derived CaO−ZrO2 heterogeneous catalyst. The optimisation of different parameters was processed by adopting a central composite design for a response−surface methodology (RSM). The experimental data were fitted to a quadratic equation employing multiple regressions and investigated by analysis of variance (ANOVA). The catalyst was exhaustively characterised by XRD, TGA, FTIR BET, SEM, TEM, CO2 TPD and XPS. In addition, the synthesized biodiesel was characterized by 1H and 13C NMR, GCMS. The physicochemical properties of the biodiesel were also reported and compared with the ASTM standards. The maximum yield that was obtained after optimization using RSM was 97.22 ± 0.4% with reaction time of 66.2 min, at reaction temperature of 73.2 °C, catalyst loading of 6.5 wt.%, and methanol−to−oil ratio of 9.7 wt.%.